2023
DOI: 10.1037/lhb0000516
|View full text |Cite
|
Sign up to set email alerts
|

The influence of race on jurors’ perceptions of lethal police use of force.

Abstract: Objective: Many highly publicized police use-of-force encounters have recently occurred in the United States. This project primarily explored whether officer, juror, or victim race affects verdicts in trials involving police use of force. Hypotheses: Because of recent conflicting research surrounding race and juror decision-making, we conducted an exploratory analysis on the interactive effects of juror, victim, and defendant race. We hypothesized that mock jurors with favorable perceptions of police legitimac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Beyond victim race, it would also be important to examine officer race, as it may provide a different lens to explore racial bias. For example, Ewanation and Maeder (2023a) found that when participants encountered a White officer in a mock trial for lethal force, they were more likely to perceive the officers' force as excessive and were more punitive in their decisions. These results have been replicated in other mock juror research Pica, Thompson, et al, 2020), indicating the race of the officer is a factor that needs further exploration within the current context.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Beyond victim race, it would also be important to examine officer race, as it may provide a different lens to explore racial bias. For example, Ewanation and Maeder (2023a) found that when participants encountered a White officer in a mock trial for lethal force, they were more likely to perceive the officers' force as excessive and were more punitive in their decisions. These results have been replicated in other mock juror research Pica, Thompson, et al, 2020), indicating the race of the officer is a factor that needs further exploration within the current context.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…A complimentary theme is the public's views of the police and, especially their use of force in encounters with civilians. Articles by Perillo et al (2023) and Ewanation and Maeder (2023) show how judgments about the use of force depend on the race of the parties involved as well as the race of the observer. Perillo and colleagues examine judgments about force in an increasingly common, yet understudied, context: police officers in school settings.…”
Section: Public Views Of the Police And Use Of Forcementioning
confidence: 99%